Australian childhood immunisation coverage, 1 April to 30 June cohort, assessed as at 30 September 2013 - Hull, Brynley P; National Centre for Immunisation Research; Surveillance (Communicable Diseases Intelligence, 2014)
The National Centre for Immunisation Research and Surveillance of Vaccine Preventable Diseases (NCIRS) provides commentary on the trends in the Australian Childhood Immunistaion Register data for children vaccinated at 12, 24 and 60 months of age.